Global changes of the RNA-bound proteome during thematernal-to-zygotic transition in Drosophila - Castello Palomares, A; Sysoev, V; Fischer, B; Frese, C; Gupta, I; Krijgsveld, J; Hentze, M; Ephrussi, A (Nature Publishing Group, 2016)
The maternal-to-zygotic transition (MZT) is a process that occurs in animal embryos at the earliest developmental stages, during which maternally deposited mRNAs and other molecules are degraded and replaced by products of the zygotic genome. The zygotic genome is not activated immediately upon fertilization, and in the pre-MZT embryo post-transcriptional control by RNA-binding proteins (RBPs) orchestrates the first steps of development. To identify relevant Drosophila RPBs organism-wide, we refined the RNA interactome capture method for comparative analysis of pre- and post-MZT embryos. We determine 523 proteins as high confidence RBPs, half of which were not previously reported to bind RNA. Comparison of the RNA interactomes of pre- and post-MZT embryos reveals high dynamicity of the RNA-bound proteome during early development, and suggests active regulation of RNA binding of some RBPs. This resource provides unprecedented insight into the system of RBPs that govern the earliest steps of Drosophila development.